Pentingnya Bimbingan Koneling Dalam Pengembangan Karir Mahasiswa Di Perguruan Tinggi - rifqi irsyadi (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2024)
The importance of counseling guidance in student career development in higher education cannot be ignored. The higher education process is not only about providing academic knowledge, but is also a critical stage in shaping students' careers and futures. Guidance counseling plays a crucial role in helping students identify their interests, talents and career goals. Guidance counseling helps students understand their potential and match it with appropriate career choices. With this support, students can make more informed decisions about the study and employment paths they will take after graduation. In addition, counseling helps overcome uncertainties and worries that often arise during the career decision-making process. Higher education institutions have a responsibility to provide effective counseling services to ensure students can reach their maximum potential. These efforts include providing information resources, career seminars, and individual counseling sessions. This way, students can develop a solid career plan, improve interpersonal skills, and understand job market trends. The importance of counseling is not only related to individual student success but also has an impact on the welfare of society. Students who are well guided in their career development are more likely to become professionals who contribute positively to society. Therefore, the integration of guidance and counseling in the tertiary environment is a must to ensure that the young generation is ready to face challenges in the world of work. Keywords: Guidance Counseling, Career Development, Students, Higher Education, Career Decisions.